South Asian masculinities : context of change, sites of continuity - Chopra, Radhika; Osella, Caroline; Osella, Filippo (Women Unlimited an associate of Kali for Women, 2004)
Selection of papers presented at the 16th European Conference on Modern South Asian Studies, University of Edinburgh, September 2000; chiefly on Indian men.